(untitled) (Gayana Botánica, 2005)
Double fluorescence in situ hybridization was used to examine the karyotype of Chaetanthera microphylla (Cass.) Hook et Arn. from Chile, including the location of 5S and 18S/25S rDNA gene sequences. The species is 2n = 24, with 8m + 4st chromosomes. Signals of 5S and 18/25S rDNA were seen in two of the 12 chromosome pairs: n° 2 and 6.